Analysis of Production Cost Calculation Using the Full Costing Method to Determine Prices Production Mainstays in Tempe Business - Ziad Imadulbilad; M. Badrun Zaman; Anisa Sains Kharisma; Nasiruddin Nasiruddin; Dwi Harini (Digital Innovation : International Journal of Management, 2025)
The purpose of this study is to determine and analyze the price main production Tempe Berkah Wasis Susanto per unit if calculated using the method full costing and difference price main production Tempe Berkah Wasis Susanto used so far with the full costing method. This type of research is a case study with the object of research Tempe Berkah Wasis Susanto business. Data collection was carried out through in-depth interviews and direct observation. Data analysis used qualitative descriptive analysis. The results of the study showed that the cost of production of Tempe Berkah Wasis Susanto per unit when calculated using the full costing method was Rp7,050 higher than the calculation results made by the business actor of Rp6,400. The cost of production using the full costing method was Rp47,516,250 higher than the calculation results used by the business actor of Rp43,050,000 with a difference of Rp4,466,250. The cost of production per unit using the full costing method was Rp7,050 higher than the calculation results made by the business actor of Rp6,400 with a difference of Rp650.